Malaria at Forest Areas in South Kalimantan, Indonesia: Risk Factors and Strategies for Elimination - Istiana, Istiana; Hadi, Usman; Dachlan, Yoes Prijatna; Arwati, Heny (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: South Kalimantan is one of province in Indonesia which has endemic area, mainly in the villages at forest area. Understanding the risk factors which can increase the risk of malaria in individuals at forest area will enable more effective use for controlling the disease. The identification of risk factors will provide information about local malaria epidemiology and usefull for making appropriate and effective malaria eradication program policies in this area. AIM: To know the risk factors of malaria prevalence in endemic forest areas in South Kalimantan, Indonesia. METHODS: This cross-sectional study was conducted on 107 adult people who lived in Batu Bulan Village and Batu Paha Village, South Kalimantan. Blood samples for malaria microscopy and rapid diagnostic test is taken from cubital vein. Household factors and demographic data were obtained. Chi-square and logistic regression were performed to analyze the factors associated with malaria prevalence in South Kalimantan. This research didn’t do vector survey, only on the prevalence of malaria and risk factor in human and environment. RESULTS: The prevalence of malaria based RDT examination was 35.5% with 23.68% Plasmodium falciparum, 21.05% Plasmodium vivax, and 55.27% mixed infection. The prevalence malaria based on microscopic examination was 17.75% with 47.36% P. falciparum, 26.32% P. vivax, and 26.32% mix infection. Demographic factors influencing the prevalence of malaria were aged below 25-years-old (p = 0.01, 95% CI, OR = 2.289), villages in Batu Paha (p = 0.048, 95% CI, OR = 3.55), and occupation as a forest worker (p = 0.022, 95% CI, OR = 6.38). House factors that influence the prevalence of malaria were the condition of the walls that are open or not tight (p = 0.048 95% CI, OR = 5.205), the roof is made of plastic (p = 0.015 95% CI, OR = 2.831), and the presence of animal cage around the house (p = 0.015 95% CI, OR = 6.292). CONCLUSIONS: Malaria incidence remains occurs with high prevalence in the pupolation in remote forest areas.